THE EFFECTIVENESS OF USING KAHOOT IN TEACHING ARABIC EXPRESSION TO IMPROVE LEARNING OUTCOMES: EFEKTIVITAS PENGGUNAAN KAHOOT DALAM PENGAJARAN EKSPRESI BAHASA ARAB UNTUK MENINGKATKAN HASIL BELAJAR - Yanti Mardiyanti; Agus Riyadi; Emas Masruroh Masruroh (Program Studi Bahasa dan Sastra Arab STIABI Riyadul 'Ulum, 2024)
The teaching of al-Ta'bir al-Araby is a new program in the field of Arabic language instruction for non-native speakers in this digital era, where this type of learning focuses on the needs of students to improve their speaking and writing skills. In this context, various issues arise in the learning process faced by instructors at the School of Humanities and Islamic Culture Riyadhul 'Ulum Tasikmalaya in the Department of Arabic Language and Literature in the 3rd semester. The low interest of students in learning is one of the reasons for the low academic performance in the al-Ta'bir al-Araby course. This study aims to test the effectiveness of using Kahoot in the al-Ta'bir al-Araby course to improve students' learning outcomes. The method used is a quantitative approach with a quasi-experimental design. The analysis methods used include tests, interviews, and written documents. The results of the study show that the use of Kahoot has a significant effect on improving students' learning outcomes in the al-Ta'bir al-Araby course.